Control of the Implementation Time of the Integrated Work Project Design and Construction of the Main Stadium Development in Papua Province (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Time control in the construction management of the "Integrated Work Project Design and Construction of the Main Stadium of Papua Province", starting from the physical planning stage, including budget utilization plans, preparation of regulations and technical requirements, as well as administrative requirements, plans for material and equipment requirements, work implementation time, manufacturing drawings and requirements. The construction was carried out by the KSO Contractor PT. Housing Development (PP) (Persero) PT. Penta Rekayasa, through an auction process. Construction Management Consultant by Consulting Services Company PT. Virama Karya (Persero). From the evaluation of the S rescedule curve, it was found that development work experienced an increase in jobs, in December 2018 the cumulative plan was 96.874%, the cumulative actual monthly progress was 96.999%. January 2019 cumulative plan 97.653%, cumulative actual monthly progress 97.890%, February 2019 cumulative plan 98.400%, cumulative actual monthly progress 98.502% and March 2019 cumulative plan 100% cumulative monthly actual 100%. From the results of the evaluation of work progress, the construction of the Papua Province Main Stadium has progressed on the plan. In the work plan (or time schedule) you can see a graph of the realization of work progress.